“Boasa Hami Ingkon Gabe Sipangoloi?” Eksistensi Perempuan Batak Dalam Film Ngeri-Ngeri Sedap - Sitorus, Novita Grace (IAKN Ambon, 2023)
Women existence is often in an ambiguous position. Women are sometimes acknowledged for their existence, but on the other hand they are also often looked down. The culture have a significant influence on understanding a woman's existence. One of them is in Batak culture, the hierarcy pattern between men and women is very thick with patrilineal elements and this is very detrimental to the existence of women in their lifes. Batak women's efforts to find their existence are often seen as a form of resistance to patriarchal culture. This is what ultimately results in women being asked to be 'obedient' figures in the sense of obeying all orders and even depending on men. This paper will look at how the existence of women in an existentialist feminist perspective, especially from Beauvoir's point of view. Existentialist feminists will dismantle the patrilineal element and reconstruct it so that the existence of women, especially Batak, is not always under the influence of men. Batak women also have the autonomous right to express opinions, to be heard, to be empowered and to dream their goals.Keywords: existence, feminist, patrilineal.